Private Immigration Detention without the Immigrants: The Subtle Use of Controlling Images in the Contemporary Era. (November 2022) - Bailey-Hall, Miara L.; Estrada, Emily P.
Scholars have well-established the socio-political and legal history of immigrant detention as a form of racialized social control in the United States. In recent years, private prison companies have benefited financially from this system, amassing sizeable profits in spite of vast criticisms and concerns. For this project, we focus on how private immigration detention—as a modern-day form of racialized social control—is normalized. Using the theoretical concept of controlling images, we examine how private prison companies frame the people they detain. Results from our analysis of 143 press releases indicate that private prisons rarely talk about the people they detain. Instead, the companies make vague and indirect references using inanimate objects which dehumanizes them. When the companies do reference migrants, they often characterize them as wards of the state, and in doing so, private prison companies are infantilizing people in lockup in subtle ways. Companies also engage in a significant amount of rhetoric that champions their organizations as they bolster their business amidst scandals and allegations. We conclude that these controlling images, while appearing race neutral, are quite effective in contributing to the invisibility of these groups and maintenance of the status quo. These actions further their exploitable quality by reproducing the oppression of racial others and simultaneously function to legitimize the business practices of private prison companies.